2020
DOI: 10.5089/9781513528571.001
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Policy, Product Market Competition, and Growth

Abstract: While there is growing evidence of persistent or even permanent output losses from financial crises, the causes remain unclear. One candidate is intangible capital – a rising driver of economic growth that, being non-pledgeable as collateral, is vulnerable to financial frictions. By sheltering intangible investment from financial shocks, counter-cyclical macroeconomic policy could strengthen longer-term growth, particularly so where strong product market competition prevents firms from self-financing their inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Using detailed balance-sheet data for the census of Italian limited liability companies for 2005-17, we show that newly-born firms were more likely to adopt highly intangible, capital-saving technologies during the 2009-12 financial recession. Incumbents instead were less likely to invest in intangible assets, in line with previous findings (Ahn et al, 2018;Manaresi and Pierri, 2019). The newcomers that adopted a newer productive mix displayed significantly higher capital productivity, but only marginally higher total factor productivity.…”
supporting
confidence: 90%
“…Using detailed balance-sheet data for the census of Italian limited liability companies for 2005-17, we show that newly-born firms were more likely to adopt highly intangible, capital-saving technologies during the 2009-12 financial recession. Incumbents instead were less likely to invest in intangible assets, in line with previous findings (Ahn et al, 2018;Manaresi and Pierri, 2019). The newcomers that adopted a newer productive mix displayed significantly higher capital productivity, but only marginally higher total factor productivity.…”
supporting
confidence: 90%
“…Seeking to explain the persistent output decline, more recent efforts have shown that intangible capital and R&D spending falls for firms facing a credit crunch in a financial crisis, and that this fall can be persistent (Aghion, Askenazy, Berman, Cette, & Eymard, 2012;Ahn et al, 2018;de Ridder, 2019;Duval et al, in press;Peia, 2019). Such crises also lead to persistent declines in productivity (Duval et al, in press).…”
Section: Literaturementioning
confidence: 99%
“…Ahn, Duval, and Sever (2018);Duval, Hong, and Timmer (in press) 2 Dell'Ariccia, Detragiache, andRajan (2008);Kroszner, Laeven, and Klingebiel (2007) 3Cerra and Saxena (2017) suggests that permanent output loss is a wider pattern for recessions generally, though financial crises tend to result in worse outcomes.4 See for instanceBaker, Bloom, and Davis (2016);Christiano, Eichenbaum, and Trabandt (2015); Gopinath, Kalemli-Özcan, Karabarbounis, and Villegas-Sanchez (2017); Reinhart, Reinhart, and Rogoff (2012);Stock and Watson (2012);Summers (2015).…”
mentioning
confidence: 99%
“…See also European Commission (2011). 128 See Ahn, Duval and Sever (2020). This box looks at the relevance of intangible capital in terms of explaining the relationship between Tobin's Q and investment, focusing on explaining estimates of an investment gap.…”
Section: Investment In Intangiblesmentioning
confidence: 99%